The Precedent Change of the Supreme Court of Appeals: The Punitive Effect of the Annulment of Negotiable Instruments on the Debtor (Upon the Decision of the Assembly of the Civil Chambers Identified As 19-1636/319, 19.3.2019) - Esra Cenkci (İstanbul Hukuk Mecmuası)
In this article, the conclusions reached in the decision of the Assembly of the Civil Chambers identified as 19-1636/319, 19.3.2019) are discussed. The aim of this study is to create a balance between the rights of the holder of an annulment decision and the bill holder, considering the status of debtor when a negotiable instrument is annulled. The Supreme Court of Appeals has decided in its previous precedents that a bill can be acquired in good faith even if it has been subjected to an annulment decision; however, the consequences of an annulment decision cannot be ignored, and it is necessary to determine who is the owner of the right arising from the bill in a case in which the bill holder and the holder of annulment decision are confronted, and afterward, the debtor can be held liable to pay to the person entitled as the right holder in this case. In this way, it has been tried to create a balance between the interests of the holder of an annulment decision, the bill holder, and the debtor by considering the effect of an annulment decision and the circulation purpose of negotiable instruments. In the decision subjected in this study, the balance was disturbed by ignoring the consequences of the annulment decision and giving priority to the acquisition of the check holder. On the other hand, an invoice for the disturbed balance was made out to the debtor by exposing him to the risk of paying twice.